Interprofessional collaboration within general practice teams following the inclusion of non-dispensing pharmacists - Thilini Sudeshika; Louise S. Deeks; Mark Naunton; Gregory M. Peterson; Sam Kosari (Taylor & Francis Group, 2023)
Abstract Background Pharmacists have been included in general practice teams to provide non-dispensing services in the Australian Capital Territory (ACT) since 2016. Interprofessional collaboration and team effectiveness are key considerations in providing high-quality patient care. These concepts have not been well studied following the inclusion of a pharmacist in general practice teams. Methods A mixed methods study was conducted to explore collaboration between pharmacists and health professionals in eight general practices in the ACT, where pharmacists were included in their teams. A validated survey instrument was adapted and utilised to assess the changes in interprofessional collaboration over time following the addition of a pharmacist. Another validated survey was utilised to explore team effectiveness at the end of the study. Semi-structured interviews, with a thematic analysis, were conducted with a purposeful sample of general practice staff members to understand the factors influencing the development of interprofessional collaboration. Results In total, 56 and 41 participants completed the baseline and follow-up survey, including 26 who completed both surveys to assess the change in collaboration over time. Interprofessional collaboration scores were high initially and did not change over time. Team effectiveness was also high at the end of the study. Twenty-one individuals participated in interviews, which generated four main interrelated themes related to interprofessional collaboration: professional working relationships, trust, commitment to collaboration, and barriers to collaboration. Trust was integral to professional working relationships and commitment to collaboration. The barriers to collaboration included not having a role description for pharmacists, inadequate interest to initiate working relationships, lack of dedicated time for interaction, lack of utilisation, and poor awareness of pharmacist-led activities in general practice. Conclusion Interprofessional collaboration was initially high and not influenced by the addition of a pharmacist, perhaps reflecting the inherent nature of the general practices willing to include a pharmacist within their team. Introducing a clear job description for pharmacists, and dedicating time to interact with pharmacists, could be beneficial in improving trust and professional working relationships and enhancing collaboration between the pharmacists and other general practice team members.